1996
DOI: 10.1001/archsurg.1996.01430150025004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Pylorus-Preserving Pancreatoduodenectomy for Chronic Pancreatitis

Abstract: In selected patients, resection of the head of the pancreas achieves long-term pain improvement in over 90% of cases. The early development of diabetes mellitus is infrequent, but over longer follow-up periods it reaches prevalence rates similar to those described in patients who have not undergone resection. Weight gain in this group was superior to that previously reported for our patients who underwent "standard Whipple" operation for chronic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 14 publications
4
46
0
5
Order By: Relevance
“…Resection of the distal bile duct in patients undergoing PD requires a bilio-enteric anastomosis, which increases the risk of ascending cholangitis and subsequent intrahepatic abscesses [17] . Following PD, the incidence of diabetes mellitus varies between 15% and 40% [18,19] . It can be noted in reports of recent papers that there is unchanged endocrine and exocrine pancreatic function following segmental pancreatic resection [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Resection of the distal bile duct in patients undergoing PD requires a bilio-enteric anastomosis, which increases the risk of ascending cholangitis and subsequent intrahepatic abscesses [17] . Following PD, the incidence of diabetes mellitus varies between 15% and 40% [18,19] . It can be noted in reports of recent papers that there is unchanged endocrine and exocrine pancreatic function following segmental pancreatic resection [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The current reported incidence of bleeding complications varies from 1% to 10%. [12][13][14]18,23,24,26,27,29,32,34,[53][54][55] A number of series from high-volume centers report a very low bleeding rate (Ͻ3%). 13,14,27,53 The incidence of bleeding complications appears to be related to the type of resection.…”
Section: Hemorrhagementioning
confidence: 99%
“…It has clearly been demonstrated that major relief of pain is achieved after standard PD, pylorus-preserving PD, and duodenum-preserving pancreatic head resection 7,8,[12][13][14][15][16]18,19,23,24 ( Table 9). Studies comparing the PD (standard and pyloruspreserving PD) to the Beger procedure indicate a superiority of the duodenum-preserving procedure.…”
Section: What Is the Clinical Effectiveness Of Pancreatoduodenectomy mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Frey's procedure, which is technically easier, can be performed with significantly lower morbidity. As mortality of resectional procedures like Whipple (68,71), Longmire-Traverso (48,72,73) or Beger (48) (47,51,66,67) has dropped to nearly nil in experienced centers, the argument of an increased mortality cannot be used any further in favor of drainage operations. However, significantly lower periand postoperative morbidity still favors the extended draining procedures.…”
Section: Results Of Surgery In Chronic Pancreatitismentioning
confidence: 99%